2012
DOI: 10.7251/bii1201024d
|View full text |Cite
|
Sign up to set email alerts
|

Uticaj profesionalnih štetnosti na invalidnost radnika zaposlenih u rudniku i termoelektrani „Ugljevik“

Abstract: Kratak sadržajUvod. Radnici u svim fazama tehnološkog procesa dobijanja uglja i električne energije, izloženi su uticaju kompleksnih i specifičnih zahtjeva rada, uz prisustvo mnogobrojnih profesionalnih štetnosti, što utiče na radnu sposobnost i nastanak invalidnosti radnika. Cilj ovog rada je utvrditi stepen, vrstu i uzroke invalidnosti radnika, i postojanje statistički značajne razlike između ovih pojava kod radnika koji rade na radnim mjestima sa posebnim uslovima rada u odnosu na one koji ne rade na takvim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the Republic of Serbia, research was conducted on the territory of the Autonomous Province of Vojvodina regarding the importance of prevention of blood-borne infections and control to reduce occupational risks among health professionals. The results of the research showed that health professionals in Vojvodina have a high rate (more than 80%) of professional exposure to these infections [16]. Similar results were obtained in our research, where 81.5% of the examined group of healthcare professionals pointed out that they were often exposed to contact with the patient's blood in their work, while 52.2% of the respondents stated that in their previous work they had an accident that resulted in contact with the patient's blood one or more times.…”
Section: Discussionmentioning
confidence: 99%
“…In the Republic of Serbia, research was conducted on the territory of the Autonomous Province of Vojvodina regarding the importance of prevention of blood-borne infections and control to reduce occupational risks among health professionals. The results of the research showed that health professionals in Vojvodina have a high rate (more than 80%) of professional exposure to these infections [16]. Similar results were obtained in our research, where 81.5% of the examined group of healthcare professionals pointed out that they were often exposed to contact with the patient's blood in their work, while 52.2% of the respondents stated that in their previous work they had an accident that resulted in contact with the patient's blood one or more times.…”
Section: Discussionmentioning
confidence: 99%